2021
DOI: 10.3390/cancers13133304
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Activation Protein Expressing Mesenchymal Cells Promote Glioblastoma Angiogenesis

Abstract: Fibroblast activation protein (FAP) is a membrane-bound protease that is upregulated in a wide range of tumours and viewed as a marker of tumour-promoting stroma. Previously, we demonstrated increased FAP expression in glioblastomas and described its localisation in cancer and stromal cells. In this study, we show that FAP+ stromal cells are mostly localised in the vicinity of activated CD105+ endothelial cells and their quantity positively correlates with glioblastoma vascularisation. FAP+ mesenchymal cells d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 67 publications
(98 reference statements)
2
18
0
Order By: Relevance
“…FAP has been identi ed as an independent biomarker associated with a poor prognosis in a growing number of cancers [20][21][22][23]. The presence of proangiogenic FAP in CAFs has been reported [9,12,24] which is consistent with our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…FAP has been identi ed as an independent biomarker associated with a poor prognosis in a growing number of cancers [20][21][22][23]. The presence of proangiogenic FAP in CAFs has been reported [9,12,24] which is consistent with our ndings.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have demonstrated that FAP is expressed by the cancer-associated fibroblasts (CAFs) that occupy the tumor microenvironment (TME) [ 17 , 18 ], and is overexpressed in 90% of epithelial tumors, including colon and breast cancers [ 19 , 20 ]. FAP expression is associated with worse prognosis as FAP supports tumor migration [ 21 ], angiogenesis [ 22 ], metastasis via matrix remodeling in TME [ 23 ], and immunomodulatory function [ 24 ]. A study by Kesch et al [ 25 ] showed that there is a significant rise in FAP expression throughout the progression of prostate cancer, in which men with advanced CRPC have the highest number of FAP-positive lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of high neovascularization in GBM have received great attention, including the presence of bizarre vessels and resistance to antiangiogenic therapy, which can be related to different types of angiogenesis [1][2][3][4][5][9][10][11][12][13][14][15][16][17]. It has been suggested that intussusception (intussusceptive microvascular growth) could be a mechanism of compensatory vascular growth occurring in human glioma [18,19], with advantages and inconveniences over classic sprouting angiogenesis [18].…”
Section: Introductionmentioning
confidence: 99%